Visualizing Embolism Propagation in Gas-Injected Leaves - Hochberg, Uri (Plant Physiol, 2019)
Because the xylem in leaves is thought to be at the greatest risk of cavitation, reliable and efficient methods to characterize leaf xylem vulnerability are of interest. We report a method to generate leaf xylem vulnerability curves (VCs) by gas injection. Using optical light transmission, we visualized embolism propagation in grapevine (Vitis vinifera) and red oak (Quercus rubra) leaves injected with positive gas pressure. This resulted in a rapid, stepwise reduction of transmitted light, identical to that observed during leaf dehydration, confirming that the optical method detects gas bubbles and provides insights into the air-seeding hypothesis. In red oak, xylem VCs generated using gas injection were similar to those generated using bench dehydration, but indicated 50% loss of conductivity at lower tension (∼0.4 MPa) in grapevine. In determining VC, this method eliminates the need to ascertain xylem tension, thus avoiding potential errors in water potential estimations. It is also much faster (1 h per VC). However, severing the petiole and applying high-pressure gas could affect air-seeding and the generated VC. We discuss potential artifacts arising from gas injection and recommend comparison of this method with a more standard procedure before it is assumed to be suitable for a given species.